CHOOSING THE STRATEGY OF INTERVAL TOLERANCES’ ASSIGNMENT - Shylo, G.M.; Vesnin, I.M.; Gaponenko, M.P. (Radio Electronics, Computer Science, Control, 2013)
Peculiarities of assigning the nominal tolerances for interval distribution law and changing the properties of components in the operation of electronic devices are considered. Interval coefficients of external influences, aging and simultaneous action of several external factors and placement of electronic components into devices are taken into account. The model of output function is formed for the worst case of external influence composition. To assign rating tolerances the coordinates of boundary points are recalculated to normal operating conditions. The optimal value of parameter deviations are obtained by equal tolerances, the maximum volume of tolerance region, the minimum cost and the optimal cost / quality relation strategies. Cost characteristic of electronic components are used. Volume tolerance is a measure of the quality. If it increases, manufacturing defects are reduced. The strategies of tolerance design are compared. Matrices of basic parameters and vertex of strategy coefficients are formed. To choose strategy the coefficients of design strategies are compared. To choose electric circuit the coefficients of tolerance design are used. The application example of proposed methods is given.